2018
DOI: 10.1038/s41477-018-0117-x
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between PTGS and TGS pathways in natural antiviral immunity and disease recovery

Abstract: Virus-induced diseases cause severe damage to cultivated plants, resulting in crop losses. Certain plant-virus interactions allow disease recovery at later stages of infection and have the potential to reveal important molecular targets for achieving disease control. Although recovery is known to involve antiviral RNA silencing, the specific components of the many plant RNA silencing pathways required for recovery are not known. We found that Arabidopsis thaliana plants infected with oilseed rape mosaic virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 44 publications
2
60
1
Order By: Relevance
“…The two DEGs DCL2 and CSD2 that were significantly up-regulated in the Ma ecotype suggest that this ecotype responded with low resources albeit rather efficiently to viral infection as demonstrated by the recovery phenotype shown by plants between 14 and 21 dpi. In agreement with the work of Kørner et al 57 our results showed that the recovery from disease symptoms probably reflected a tolerant state against the potyviral infection characterized by low levels of viral RNA and accumulation of vsiRNAs. Other recent reports documented the beneficial impact on plant resilience to drought and other abiotic stress derived from maintaining a virus infection in leaves recovered from disease symptoms 58 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The two DEGs DCL2 and CSD2 that were significantly up-regulated in the Ma ecotype suggest that this ecotype responded with low resources albeit rather efficiently to viral infection as demonstrated by the recovery phenotype shown by plants between 14 and 21 dpi. In agreement with the work of Kørner et al 57 our results showed that the recovery from disease symptoms probably reflected a tolerant state against the potyviral infection characterized by low levels of viral RNA and accumulation of vsiRNAs. Other recent reports documented the beneficial impact on plant resilience to drought and other abiotic stress derived from maintaining a virus infection in leaves recovered from disease symptoms 58 .…”
Section: Discussionsupporting
confidence: 93%
“…Vpg is the other VSRs coded by PVY and is involved in suppression of RNA silencing by the degradation of suppressor of gene silencing 3 (SGS3), which occurs via both the 20 S ubiquitin-proteasome and autophagy pathways 56 . SGS3 is crucial for the synthesis of virus-derived dsRNAs necessary for vsiRNAs production and together with DCL4 is a key component in the interaction with RDR6 for the appearance of the recovery phenotype in virus-infected plants 57 . We observed recovery from symptoms induced by PVY C -to infection in Ma plants and in all plants of the three graft combinations but not in UC plants and nonetheless we could not specifically associate the presence/absence of the recovery to a significative up-/down-regulation of SGS3, which was not detected among the 91 DEGs exclusively modulated in UC infected plants compared to mock-inoculated controls ( Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Such pathways possibly act additively to but independently of the coilin‐mediated mechanism described in this paper because neither coilin KD nor deletion in 16K affected expression of the RDR2 , RDR6 , DCL and AGO genes that are known to be involved in both post‐transcriptional and transcriptional gene silencing (PTGS or TGS) (Figs c, S4). In contrast to the coilin‐mediated mechanism described here for the TRV pathosystem, plant recovery from ORMV is determined by components of PTGS or TGS pathways (Kørner et al ., ). Collectively these data support the idea that the recovery processes in different plant–virus interactions are associated with a diverse range of defence mechanisms (Ghoshal & Sanfaçon, ).…”
Section: Discussionmentioning
confidence: 97%
“…RNA silencing is a transcriptome regulation mechanism that uses small RNAs (sRNAs) as guides and that can act transcriptionally by cytosine DNA methylation via Transcriptional Gene Silencing (TGS) or post-transcriptionally (PTGS) by cleavage of RNA targets (Borges and Martienssen, 2015; Castel and Martienssen, 2013; Kørner et al ., 2018) to regulate gene expression, modify chromatin topology or defend against viral infections (Baulcombe, 2004). In this context, the RNA-directed DNA methylation (RdDM) pathway is a methylation mechanism that can occur in different cytosine sequence contexts directed by 24-nt sRNAs (Gallego-Bartolomé et al ., 2019; Law and Jacobsen, 2010).…”
Section: Introductionmentioning
confidence: 99%